Quantitative Characteristics And Variability Of Cocoa (Theobroma Cacao) In Koto Salak District, Dharmasraya Regency - Ririn Eka Putri; Gustian; Dede Suhendra (Jurnal Riset Perkebunan, 2022)
Exploration and characterization of germplasm is an important stage in plant breeding activities. The present research was about exploration and morphological characterization of cacao (Theobroma cacao L.) in smallholder plantations in Koto Salak Sub-district, Dharmasraya Distric. It was carried out on July until October 2021. The objectives of this study were to characterize the morphology of cacao crops in Koto Salak Sub-district, Dharmasraya District and to determine the diversity level of cacao crops in that area. This research was by a survey method, with purposive sampling. The technique for data collection was by observe the morphology of the plants in each sample. The obtained data were analyzed descriptively, and for the similarity analysis, statistical calculation was by the NTSYS Ver 2.02 program. The research results obtained 4 variants of cacao plants which collected from 5 villages namely Padukuan, Pulau Mainan, Simalidu, Koto Salak, and Ampalu. Researcher obtained 30 samples of cacao plants which characterized by 16 characters, characters were wide variability and 14 other characters narrow variability with the level of diversity ranging from 39-77%.